UJI EFEKTIVITAS PESTISIDA NABATI TERHADAP MORTALITAS DAN INTENSITAS SERANGAN ULAT GRAYAK (Spodoptera litura Fabricus) PADA TANAMAN SAWI (Brassica juncea L.): TEST THE EFFECTIVENESS OF BOTANICAL PESTICIDES ON MORTALITY AND INTENSITY OF ARMYWORM (Spodoptera litura Fabricus) ON MUSTARD PLANT (Brassica juncea L.) - Salsa Malikal Mulki; Sugiarto; Lutfi Afifah (Agrifarm : Jurnal Ilmu Pertanian, 2022)
Armyworm (Spodoptera litura F.) is one of the important pests on the plant mustard greens. The purpose of this research is to get the type of pesticide that is effective gives the highest effect on mortality and the intensity of the attack armyworm (Spodoptera litura F.) in the mustard plant (Brassica juncea L.). The method used is the experimental method while the design of experiment used was Complete Random Design (RAL) a single factor for the observation of mortality and a Randomized block Design (RAK) single factor for the observation of the intensity consisting of 8 treatments with 4 replications. The standard treatment P0 (Control/No Treatment), P1 (Papaya Leaf Extract 300 g/l), P2 (Papaya Leaf Extract 500 g/l), P3 (Extract of the Stem of Lemongrass 120 g/l), P4 (Extract of the Stem of Lemongrass 160 g/l), P5 (Extract of Neem Leaves 300 g/l), P6 (Extract of Neem Leaves 500 g/l) and P7 (Karbosulfan 2ml/l). The results showed that the application of some type of pesticide (Papaya Leaf Extract 300 g/l), (Papaya Leaf Extract 500 g/l), (Extract of the Stem of Lemongrass 120 g/l), (Extract of the Stem of Lemongrass 160 g/l), (Extract of Neem Leaves 300 g/l) and (Extract of Neem Leaves 500 g/l) gives a real influence on the mortality and the intensity of the attack armyworm (Spodoptera litura F.) in the mustard plant (Brassica juncea L.) varieties of Tosakan. Types of vegetable pesticides Neem Leaf Extract 500 g/l (treatment P6) gave the highest mortality of 87.50%, the lowest attack intensity 57,37%, the lowest larval weight 0.34 g, the lowest pupa weight 0.04 g, with an average LT50 value of 4-5 days and produced the highest plant weight of 10.81 g. Keywords: Intensity of S. litura; Mortality; LT50 and Pesticide.